Short communication: Nanoscale heterogeneity of U and Pb in baddeleyite from atom probe tomography – 238U series alpha recoil effects and U atom clustering - S. Denyszyn; D. W. Davis; D. Fougerouse (Geochronology)
Atom probe tomography (APT) of 238U and 206Pb has been applied to baddeleyite crystals from the Hart Dolerite (1791±1 Ma) and the Great Dyke of Mauritania (2732±2 Ma) in an effort to constrain the average nuclear recoil distance of 238U series daughter nuclei and correct alpha-recoil-induced Pb loss on U–Pb ages from small baddeleyite crystals. The Hart Dolerite sample showed no variations in Pb concentrations near the edge and is interpreted to represent a cleaved surface instead of the original crystal surface. The Great Dyke sample shows U zoning, and the associated 206Pb zoning is affected by alpha recoil, apparently adjacent to a natural grain surface. This sample also shows primary clusters of U atoms at a scale of 10 nm that contain about 40 % of the total U. 207Pb/206Pb<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="63pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="9590d5bb286e4785cc85b0e80b1ddaa8"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="gchron-6-607-2024-ie00001.svg" width="63pt" height="15pt" src="gchron-6-607-2024-ie00001.png"/></svg:svg> nanogeochronology suggests that the clusters are primary in origin; however, they are too small to constrain alpha recoil distance beyond a few nanometres. To constrain alpha recoil distance, a forward-modelling approach is presented where 206Pb redistribution functions were determined for a range of possible recoil distances. Synthetic 206Pb/238U<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="57pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="976d5de522f5330a2ea037e20b88a23d"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="gchron-6-607-2024-ie00002.svg" width="57pt" height="15pt" src="gchron-6-607-2024-ie00002.png"/></svg:svg> profiles were determined from the convolution of the observed U profile with the redistribution functions for different alpha recoil distances. These were compared to the observed 206Pb/238U<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="57pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="670fd7957233d6dbb6ac2b3c5c377077"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="gchron-6-607-2024-ie00003.svg" width="57pt" height="15pt" src="gchron-6-607-2024-ie00003.png"/></svg:svg> profile to determine the recoil distance that gives the best fit. The observed U zoning was extrapolated to account for the full range of possible alpha recoil redistribution effects, which is larger than the 40 by 400 nm size of the APT field of view. Any reasonable extrapolation constrains the average alpha recoil distance to over 70 nm, which is much larger than previous estimates using other methods. This could be because recoil distances can be highly anisotropic within small crystal samples or because laterally non-uniform U zoning was a factor that modified the recoiled Pb distribution. APT is a potentially useful approach for determining average alpha recoil distance but requires sampling of primary smooth crystal faces with demonstrably uniform zones.